Pathogenic Characteristics of Staphylococcus aureus Endovascular Infection Isolates from Different Clonal Complexes - Pérez-Montarelo, Dafne; Viedma, Esther; Murcia, Mercedes; Muñoz-Gallego, Irene; Larrosa, Nieves; Brañas, Patricia; Fernández-Hidalgo, Nuria; Gavaldà, Joan; Almirante, Benito; Chaves, Fernando (Frontiers in Microbiology, 2017)
Staphylococcus aureus is a major cause of bacteremia and, even with appropriate clinical management, causes high morbidity and mortality due to its involvement in endovascular complications and metastatic infections. Through different pathogenic in vivo and in vitro models we investigated the behavior of S. aureus most relevant clonal complexes (CCs) causing endovascular complications. We analyzed 14 S. aureus strains representing CC5, CC8, CC15, CC30 and CC45 that caused endovascular complications, including methicillin susceptible and resistant isolates and strains with different functionality of the agr global regulator. Their adherence to collagen, interaction with the endothelium, resistance to immune attack, capacity to form biofilm and virulence in the Galleria mellonella model were analyzed. CC30 and CC45 showed greater adhesion to collagen and CC8 showed a trend towards higher rate of intracellular persistence in endothelial cells. All CCs exhibited similar tolerance to neutrophil antimicrobial peptide hNP-1 and were capable of forming biofilms under static conditions. The virulence assay in the Galleria mellonella model demonstrated that CC15 and CC30 were the most and least virulent, respectively. The analysis of the genomic sequences of the most relevant virulence genes identified some CC15 specific gene patterns (absence of enterotoxins and sak gene) and variants (mainly in leucocidins and proteases), but did not reveal any gene or variant that could be responsible for the increased virulence detected for CC15 strains. Even though all the CCs were capable of causing endovascular complications, our results showed that different CCs are likely to produce these complications through different mechanisms which, if confirmed in more sophisticated models, would indicate the need to more specific management and therapeutic approaches.